Stance of Sports and Fitness: A Scientometric Review - Davi Sofyan; Yudha Munajat Saputra; Juntika Nurihsan; Nurlan Kusmaedi; Khairul Hafezad Abdullah (OVS LLC, 2022)
Sport and fitness are physical requirements in the same way that humans require food and water. On the other hand, sport and fitness is a highly complex field of study, complicating attempts to define critical terms, resulting in a relative lack of scientometric analysis. The study goal is to look at the development of sport and fitness research around the world, using the Scopus and Web of Science databases as its foundation. Materials and methods. Publications are gathered using the Scopus and Web of Science databases as well as scientometric parameters, including worldwide publication trends, the authors who receive the most citations, the amount of citations, and author keywords. Results. The results show the authors' keywords analysis was inspected based on their relationship to physical activity, physical exercise, and physical training. The United States was the most active country, with 601 publications. As expected, the United States is a leader in physical activity promotion, with 19.3 percent of the population participating in sports and exercising daily in 2019. The International Journal of Environmental Research and Public Health from Switzerland leads 68 publications, which is another noteworthy finding. Additionally, according to this analysis, Ortega, F.B., of the School of Medicine, University of Granada, Madrid, Spain, is the author who publishes the most documents with 33 in total. Conclusions. According to our research, the top five keywords that gained traction over the previous two years were "Cardiorespiratory Fitness," "Body Composition," "Health," "Physical Activity," and "Adolescents." The study value to the field of sports and fitness is that it provides readers and upcoming researchers with a wide range of sports and fitness trends from the past and present. Additionally, the study findings will aid future academics in predicting potential industry trends.